Pengaruh Advertising, Financial Literacy, dan Personal Selling Terhadap Keputusan Menjadi Nasabah Koperasi Simpan Pinjam Dalam Perspektif Bisnis Islam : Studi Pada BMT Assyafi’iyah Kc. Sumberagung Pringsewu - Khamelia Khoirunnisa; Ersi Sisdianto; Adib Fachri (Jurnal Penelitian Ilmu Ekonomi dan Keuangan Syariah, 2025)
This study is motivated by the increasing competition among cooperatives and the declining number of members at BMT Assyafi’iyah in recent years. This condition indicates the presence of various factors influencing people's decisions in choosing Islamic financial institutions. The purpose of this research is to analyze the influence of advertising, financial literacy, and personal selling on the decision to become a member of a savings and loan cooperative from the perspective of Islamic business principles. The research was conducted at BMT Assyafi’iyah, Sumberagung District, Pringsewu, involving 89 respondents selected through purposive sampling. A quantitative approach was used with the Partial Least Squares-Structural Equation Modeling (PLS-SEM) method. Data were collected through questionnaires and analyzed using statistical techniques. The results show that advertising has no significant effect on membership decisions, while financial literacy has a significant influence, and personal selling is the most dominant factor. These findings suggest that financial understanding and direct interaction are more effective in attracting prospective members than advertising strategies.